EXPERIMENTAL STUDY ON HIGH PERFORMANCE CONCRETE USING DIFFERENT TYPES OF AGGREGATE - Magesh, Mr. A.; Kumar, Mr.S.Udaya (IJRDO - Journal of Mechanical And Civil Engineering, 2017)
A new generation of concrete, High performance of concrete has been developed of its outstanding strength durability performance shows a very promising future in construction application in this paper several possibilities are examined for reducing the price of producing high performance concrete and to minimize the ability of normal concrete. The following types of coarse aggregate were used to produce the concrete; secondary aggregate; marble; light weight aggregate (pumice) and natural mineral (gravel). The concrete contain a highly effective Super plasticizer and metakoline. Mechanical properties and water absorption sharply increased during early stage approaching asymptotic valves, depending on design strength codes. Results of 28 days of curing light weight aggregate gives the high mechanical properties. When estimated with the conventional concrete. These experimental results demonstrate that the light weight aggregate strongly influences the mechanical and durability properties without basic properties of concrete.